Emotions in Command : Biology, Bureaucracy, and Cultural Evolution - Salter, Frank Kemp (London Transaction Publishers, 2009)
Reviews the social science literature showing the place of ethological methods and concepts, and aspects of the evolution and physiology of dominance and affiliation. This book introduces the emotional underpinnings of dominance and affiliation, and applies these concepts in a summary of the literature on interpersonal signaling.
Include Illustrations, Maps, References and Index
Keywords: Social control -- Organizational behavior -- Dominance (Psychology) -- Hierarchies